Factors Influencing Enrollment in the Medication Therapy Management Clinic at an Academic Ambulatory Care Clinic. (April 2016) - Shah, Mansi; Tilton, Jessica; Kim, Shiyun
Purpose: In 2001, the University of Illinois Hospital and Health Sciences System (UI Health) established a pharmacist-run, referral-based medication therapy management clinic (MTMC). Referrals are obtained from any UI Health provider or by self-referral. Although there is a high volume of referrals, a large percentage of patients do not enroll. This study was designed to determine the various factors that influence patient enrollment in the MTMC. Methods: This study was a retrospective chart review of demographic and patient variable data during years 2010 and 2011. Disabilities, distance from MTMC, mode of transportation, past medical history, and appointment dates were extracted from the medical records. Results were analyzed using descriptive statistics and logistic regression analysis. Results: A total of 103 referrals were made; however, only 17% of patients remain enrolled in MTMC. The baseline demographics included a mean age of 63 years, 68% female, 70% African American, and 81% English speaking. Patients lived an average of 8 miles from MTMC; most utilized public or government-supplemented transport services; 24% of patients reported some type of disability, most commonly utilizing a walker or a wheelchair. On average, patients were prescribed 13 medications with hypertension (70%), diabetes (56%), and hyperlipidemia (48%) being the most common chronic disease states. The reason for referral included medication management, education, medication reconciliation, and disease state management. Five patients were unable to be contacted to schedule an initial appointment. Additionally, 18 patients failed their scheduled initial appointment and did not reschedule. Logistic regression analysis demonstrated distance traveled for clinic visit, age, and history of hypertension affected the probability of patients showing for their appointments (chi-square = 19.7, P < .001). Conclusion: This study demonstrated that distance from MTMC is the most common barrier in patient enrollment; therefore, strategies to improve patient access are necessary.